Cognitive dissonance resolution depends on executive functions and frontal lobe integrity. (June 2021) - Tandetnik, Caroline; Sohier, Elisa; Capelle, Laurent; du Boullay, Viviane; Obadia, Michael; Chammat, Mariam; Pyatigorskaia, Nadya; Naccache, Lionel
Abstract: The free choice paradigm constitutes one of the most explored paradigms of cognitive dissonance research. Typically, once asked to choose between two similarly rated items, subjects subsequently exhibit an increased preference for chosen items and a decreased preference for rejected ones. Recent studies have demonstrated that such choice-induced preference change (CIPC) occur exclusively for remembered choices, suggesting a mechanism that ensures subjective coherence across time. In the present work we predicted that in order for CIPC to occur, not only must past choices be remembered, but executive networks responsible for detecting and solving conflicts must also be functioning. We confirmed this prediction in a group of patients with frontal lobe lesions. While non-dysexecutive (NODYS) patients behaved as their matched controls did, dysexecutive (DYS) patients failed to change their subjective preferences even when they could remember their previous choices. We have therefore demonstrated the crucial role of executive functions mediated by the frontal lobe in cognitive dissonance resolution.